Community Service Activities – Education And Skin Hydration Screening For Productive Age Group - Sukmawati Tansil Tan; Alexander Halim Santoso; Ernawati Ernawati; Yohanes Firmansyah; Joshua Kurniawan; Jasmine Syabania Noviantri (Universitas 17 Agustus 1945 Semarang, 2023)
Hydration of the epidermis refers to the maintenance of the skin's natural moisture balance. This is accomplished by providing and sustaining an adequate level of moisture in the skin layer. Hydration of the skin is essential for sustaining healthy and beautiful skin, as well as preventing skin issues like dryness, redness, irritation, and premature aging. The Skin Hydration Counseling and Screening activities seek to prevent dry skin issues by educating the public on the significance of maintaining skin hydration. Through this activity, participants learned about the risk factors for dry skin, the significance of using the proper moisturizer, and how to keep the skin nourished. In addition, screenings are conducted to detect skin hydration issues early on and provide treatment recommendations. It is hoped that by increasing people's knowledge and understanding of skin hydration, they will adopt appropriate care practices and prevent dry skin from occurring. This activity contributes significantly to participants' improved skin health and quality of life.